The modern spirit of Asia the spiritual and the secular in China and India - Veer, Peter van der (Princeton University Press, 2014)
"The Modern Spirit of Asia challenges the notion that modernity in China and India are derivative imitations of the West, arguing that these societies have transformed their ancient traditions in unique and distinctive ways.Peter van der Veer begins with nineteenth-century imperial history, exploring how Western concepts of spirituality,secularity, religion, and magic were used to translate the traditions of India and China. He traces how modern western notions of religion and magic were incorporated into the respective nation-building projects of Chinese and Indian nationalist entellectuals, yet how modernity in China and India is by no means uniform. While religion is a centerpiece of Indian nationalism, it is viewed in China as an obstacle to progress that must be marginalized and controlled." -- Publisher website